2004
DOI: 10.1007/s00284-004-4267-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Characterization of a Novel, Oil-Degrading Bacterium, Pseudomonas aeruginosa T1

Abstract: A novel, oil-degrading bacterium (strain T1) was isolated from a hot spring in Hokkaido, Japan. It efficiently degrades different types of fats and oils, including edible oil waste. When grown in a mineral salt medium containing 1% triacylglycerol (as salad oil), hydrolysis products were 1,3- and 1,2-diacylglycerols, monoacylglycerol, and free fatty acid. However, these products were almost completely consumed during cultivation at 30 degrees C for 5 days, indicating that extracellular lipase acts randomly at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…The samples were transferred to the laboratory and were spread on Luria-Bertani (LB) agar (1% NaCl, 1% tryptone, 0.5% yeast extract and 1.5% agar) plates and incubated at 37°C for 24 h on the same day. Samples were enriched using the method of Hasanuzzaman et al (2004) …”
Section: Samples Collection and Enrichmentmentioning
confidence: 99%
“…The samples were transferred to the laboratory and were spread on Luria-Bertani (LB) agar (1% NaCl, 1% tryptone, 0.5% yeast extract and 1.5% agar) plates and incubated at 37°C for 24 h on the same day. Samples were enriched using the method of Hasanuzzaman et al (2004) …”
Section: Samples Collection and Enrichmentmentioning
confidence: 99%
“…Pseudomonads are effective degraders capable of utilizing a wide range of simple and complex organic compounds (Hasanuzzaman et al, 2004). However, no report on degradation of methylindoles by Pseudomonas aeruginosa is available.…”
Section: Characterization Of Indolic Compounds Degrading Bacteriamentioning
confidence: 99%
“…Other studies indicated that, pathogenic bacteria such as P. aeruginosa able to utilize crude oil can be isolated from the environment (Chaerun et al, [11]; Hasanuzzaman et al, [12]). However, none of the medical strains grew in the presence of crude oil.…”
Section: Resultsmentioning
confidence: 99%